2012
DOI: 10.1016/j.tips.2011.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and modularity of G protein-coupled receptor structures

Abstract: G protein-coupled receptors (GPCRs) comprise the most “prolific” family of cell membrane proteins, which share a common mechanism of signal transduction, but greatly vary in ligand recognition and function. Crystal structures are now available for rhodopsin, adrenergic, and adenosine receptors in both inactive and activated forms, as well as for chemokine, dopamine, and histamine receptors in inactive conformations. Here we review common structural features, outline the scope of structural diversity of GPCRs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
335
1
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 401 publications
(353 citation statements)
references
References 87 publications
5
335
1
6
Order By: Relevance
“…5, blue circle) and H8 (site 404) (Fig. 5, orange circle) as well as previous biophysical and crystallographic studies of other GPCRs (10,39). The model shows no changes in the antagonist bound state (R) (Fig.…”
Section: Sdfl Studies Confirm That Org 27569 Traps the Receptor In A supporting
confidence: 76%
“…5, blue circle) and H8 (site 404) (Fig. 5, orange circle) as well as previous biophysical and crystallographic studies of other GPCRs (10,39). The model shows no changes in the antagonist bound state (R) (Fig.…”
Section: Sdfl Studies Confirm That Org 27569 Traps the Receptor In A supporting
confidence: 76%
“…The extracellular region (comprising the N terminus of the protein) is characterized by a high structural diversity allowing the recognition of a wide spectrum of ligands. Interhelical bonds and hydrophobic interactions between highly conserved residues in GPCR provide the stability of the TM region (Palczewski et al, 2000;Katritch et al, 2012), which also harbors a number of kinks elicited by Pro residues, segregating the receptor into ligand binding and receptor signaling 'modules' (Latek et al, 2012). As shown by crystallographic studies, the overall structure of GPCR proteins is highly conserved, but significant diversities can be observed in the loop regions and in the pitch and orientation of individual TM in the helical bundle (Lu and Wu, 2016).…”
Section: Structural Biology Of Receptor Complexesmentioning
confidence: 99%
“…Although technically in an inactive state, it has been shown that large-scale movements of amino acid residues in the orthosteric binding site of class A GPCRs are not requisite for activation of the receptor [26]. In addition, it has been found that virtual screening for ligands using inactive-state GPCRs can produces agonist leads (see for example Negri et al) [27].…”
Section: Molecular Modelingmentioning
confidence: 99%